Assessing vulnerability in Cochabamba, Bolivia and Kota, India: how do stakeholder processes affect suggested climate adaptation interventions?. Issue 1 (2nd January 2018) - Wilk, Julie; Jonsson, Anna C.; Rydhagen, Birgitta; del Callejo, Ivan; Cerruto, Noelia; Chila, German; Encinas, Silvia; Kumar, Arun; Rani, Ashu
ABSTRACT: In Cochabamba, the vulnerability assessment process focused on La Maica community and the agriculture sector. Community stakeholders were involved in workshops while municipal and regional actors participated through interviews. In the Kota process, the municipality was in the geographical focal point and a multi-level stakeholder group focused upon slum inhabitants. The suggested interventions and actions in both cities were dominated by systems (infrastructure and ecosystems) while identified barriers and facilitating factors to implementation revealed a greater acknowledgement of governance issues. Focus on marginalized groups and sectors is facilitated by the direct representations of those issues. While multi-stakeholder processes can be important forums for social learning adaptation planning that benefit vulnerable sectors and groups, with limited inclusion and responsibility given to representatives of marginalized sectors and groups for implementation actions, it is likely that the interests and priorities of more powerful actors will dominate and not contribute to increasing the resilience of the most vulnerable.